Association between asymptomatic intracranial arterial stenosis and insulin resistance or diabetes mellitus: a cross-sectional study in rural Shandong, China. Issue 2 (4th December 2020) - Wang, Qiao; Zhao, Yuanyuan; Wang, Xiang; Ji, Xiaokang; Sang, Shaowei; Shao, Sai; Ma, Xiaotong; Wang, Guangbin; Lv, Ming; Xue, Fuzhong; Du, Yifeng; Sun, Qinjian
Abstract : Introduction: Recent studies have shown that insulin resistance (IR) is correlated to atherosclerosis development. However, few studies have investigated the association between IR and asymptomatic intracranial arterial stenosis (aICAS). Research design and methods: This cross-sectional study enrolled 2007 rural residents in China who were aged ≥40 years without a clinical history of stroke and transient ischaemic attack. We used transcranial Doppler ultrasonography in combination with magnetic resonance angiography to diagnose aICAS (stenosis ≥50%). IR was defined as a homeostasis model assessment of insulin resistance ≥3.0 based on the 75th percentile for all the participants. Multivariate logistic regression models were employed to assess the relationship of diabetic parameters with aICAS in all participants, as well as with aICAS in non-diabetic participants, and further stratified by sex. Results: After adjusting for age, gender, smoking habit, drinking habit, low-density lipoprotein cholesterol, raised blood pressure, triglycerides, high-density lipoprotein cholesterol and waist circumference, diabetes mellitus (DM) (OR=2.09, 95% CI 1.31 to 3.32), fasting plasma glucose (FPG) (OR=1.34, 95% CI 1.14 to 1.57), and IR (OR=1.75, 95% CI 1.11 to 2.75) were associated with aICAS in the total study population; however, these relationships remained significant only in men after the analyses were stratified by sex (DM: OR=3.40, 95% CI 1.62 to 7.13; FPG: OR=1.64, 95% CI 1.26 to 2.13; IR: OR=3.04, 95% CI 1.44 to 6.42). When further excluding the diabetic participants from the total study population, positive associations between IR and aICAS were similarly observed only in men (OR=4.65, 95% CI 1.69 to 12.82). Conclusions: IR might predict the prevalence of aICAS independently of major cardiovascular risk factors and metabolic syndrome components among men living in rural China.